1984
DOI: 10.1111/j.1365-2214.1984.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual, kinaesthetic and cross‐modal judgements of length by clumsy children: a comparison with young normal children

Abstract: In a previous study, clumsy children, when compared to normal children of the same age, were found to be impaired in their ability to match the length of successively presented straight lines within and between the modalities of vision and kinaesthesis. The present study explores this finding further by comparing the clumsy children's performance with that of a group of younger normal children whose skills of movement are comparable to those of the clumsy children. It was found that the clumsy children's perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 7 publications
4
17
0
Order By: Relevance
“…Pointing with the non-preferred hand reflected the findings when the scores of the two hands were combined, i.e. significant differences, in favour of the control children, in the three conditions V, VH and H. These results support both the visual deficit hypothesis and the findings from studies that have suggested that difficulties in processing felt (kinaesthetic) information are largely responsible for impaired perceptuo-motor performance (Laszlo and Bairstow 1985;Laszlo et al 1988;Hulme et al 1982aHulme et al , 1984.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Pointing with the non-preferred hand reflected the findings when the scores of the two hands were combined, i.e. significant differences, in favour of the control children, in the three conditions V, VH and H. These results support both the visual deficit hypothesis and the findings from studies that have suggested that difficulties in processing felt (kinaesthetic) information are largely responsible for impaired perceptuo-motor performance (Laszlo and Bairstow 1985;Laszlo et al 1988;Hulme et al 1982aHulme et al , 1984.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the results of earlier studies, in which scores derived from only the preferred hand or a combination of both hands were used Hulme et al 1982aHulme et al , 1984Smyth 1991Smyth , 1994, might need to be qualified. At the same time, they point to possible underlying neurological disorders in the HECP children that might mediate in the poor performance with the non-preferred hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some disagreement in the literature over whether children should be introduced to handwriting techniques before they are perceptually mature enough to cope with the perceptual dimensions this entails (Bryant, 1974;Hulme, 1988). This assumption undermines the Teodorescu programme and questions its feasibility.…”
Section: Discussionmentioning
confidence: 96%
“…Children with DCD present with a wide range of deficits including the use of proprioception [3,4], visuo-spatial perception [5,6] and response selection [7]. However, it is not clear if the visual-motor deficits seen in these children extend to perceptual tasks with a visual demand but no motoric component.…”
Section: Introductionmentioning
confidence: 98%